What is Leisure Without Becoming? Assemblages of Active and Reactive Leisure. (3rd September 2019) - Stalker, Glenn J.
Abstract: In answering the question, "what is leisure without becoming?" this article revisits philosophical insights in Deleuze's reading of Spinoza and Nietzsche. I investigate the relevance of these thinkers to Deleuze and Guattari's collaboration to propose an understanding of leisure as not only becoming but also as negation of difference and possible repetition of the same in reactive leisure. Leisure as becoming is a vital realization of what a body can do that cannot entirely be conceived as a state of Being, a period of time, or necessarily an activity. Deleuze and Guattari's theory of assemblage is used to understand becoming as a line of flight, a relational deterritorialization, that extends the capacities of a body.